(untitled) (Social Science Review, 2022)
Under nutrition is common in children with cerebral palsy (CP) due to oromotor dysfunction and feeding difficulties. Responsive feeding is a growing concern in nutrition field as a potential intervention for caregiver’s behaviour change during feeding. This study was designed to identify the feeding style of caregiver and the role of responsive behaviour on food refusal and nutritional status of young children with CP. This was a cross-sectional mix method study. Participants were children with CP aged between 18-36 months. 66 caregiverchildren were selected as quantitative sample and 11 mothers were included in two focused group discussions for qualitative data. Children’s feeding session for one main meal was videotaped at a rehabilitation centre. Feeding styles were coded as active and responsive behaviour which was further categorized into positive and negative behaviour. Nutritional status was measured as weight for age z scores. Caregivers mostly used active behaviour than responsive and more positive behaviour than negative. The relation between feeding style and food refusal was found and negative behaviour was related with increased food refusal. Significant relationship was found between caregiver’s active and positive behaviour and child’s active behaviour. More than half of the children with CP were underweight for their age. No significant relation appeared between weight for age z score and caregiver’s feeding style. Social Science Review, Vol. 38(1), June 2021 Page 217-248